Morphometric characteristics of Mojosari and Alabio ducks in Indonesia - Fitra, Ardian; Ciptadi, Gatot; Nurgiartiningsih, Veronica Margareta Ani (Jurnal Ilmu-Ilmu Peternakan, 2024)
This study investigated the morphometric characteristics of Mojosari and Alabio ducks, indigenous breeds recognized for their genetic value in Indonesian agriculture. A total of 456 ducks, comprising 254 Mojosari and 202 Alabio ducks, were assessed for body weight (BW), shank length (SL), breast circumference (BrC), and back length (BcL) at 10 weeks of age. Descriptive statistics were used to summarize morphometric traits, and the Mann?Whitney U test was applied to evaluate differences between sexes due to the nonnormal distribution of the data. Additionally, Spearman correlation analysis was conducted to examine the relationships between body weight and morphometric traits, identifying reliable predictors across sexes and breeds. Significant breed- and sex-specific variations were observed, with male Alabio ducks showing superior body weights, whereas female Mojosari ducks presented distinctive shank proportions, reflecting potential adaptive differences. Correlation analysis highlighted back length and breast circumference as strong predictors of body weight, with a greater association observed in female Alabio ducks. These findings provide a foundational understanding of morphometric diversity in Indonesian ducks, supporting their conservation and potential for targeted breeding programs to increase productivity, resilience, and adaptability.